POLA PENGELOLAAN KEUANGAN KELUARGA PADA IBU RUMAH TANGGA (STUDI PADA IBU RUMAH TANGGA YANG BEKERJA SEBAGAI CLEANING SERVICE DI UIN SULTAN SYARIF KASIM RIAU) - Sitti Rahmah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2014)
This study aims to determine the background of women or housewives worked as a cleaning service at UIN Suska Riau and to determine the pattern of family financial management of women or housewives who worked as a cleaning service at UIN Suska Riau. The study was conducted at UIN Suska Riau with the object of research is a housewife who works as a cleaning service at UIN Suska Riau. Data collection techniques used are in-depth interviews with data analysis techniques using qualitative analysis. The results showed that the reason women or housewives worked as a cleaning service at UIN Suska Riau is due to the social and economic aspects. In managing the family finances, respondent does not meet the criteria of good management, because the proper management must meet the following stages, namely stages of planning, implementation, and assessment stages or controlling. However, in the family housewives of new cleaning service only carry out planning stages, while implementing and controlling have not been implemented properly